2016
DOI: 10.1186/s13030-016-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for job burnout with a mobile health web application using questionnaire data: a proof of concept study

Abstract: BackgroundJob burnout has become a rampant epidemic in working societies, causing high productivity loss and healthcare costs. An easy accessible tool to detect clinically relevant risk may bear the potential to timely avert the dire sequelae of burnout. As a start, we performed a proof of concept study to test the utilization of a mobile health web application for a free and anonymous burnout risk assessment with established questionnaires.MethodsWe designed a client-side javascript web application for users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…48,49 Job burnout may lead to helplessness, despair, sleep problems, and exhaustion and ultimately affect physical and mental health, which are highly associated with QOL. 50 Analysis of data in this study showed that nurses' QOL was lower when they reported a higher level of burnout, which is consistent with Suner's study. 48 The higher the job burnout was, the lower the QOL the nurses experienced, which was in agreement with Khamisa's study that showed nurses had high levels of job burnout and poor general health.…”
Section: Discussionsupporting
confidence: 89%
“…48,49 Job burnout may lead to helplessness, despair, sleep problems, and exhaustion and ultimately affect physical and mental health, which are highly associated with QOL. 50 Analysis of data in this study showed that nurses' QOL was lower when they reported a higher level of burnout, which is consistent with Suner's study. 48 The higher the job burnout was, the lower the QOL the nurses experienced, which was in agreement with Khamisa's study that showed nurses had high levels of job burnout and poor general health.…”
Section: Discussionsupporting
confidence: 89%
“…A campaign was launched via Medinside, Winsider AG, Winterthur, Switzerland, an open access portal for the health care sector, particularly recruiting physicians, as they show high prevalence of burnout 14 . Data were collected with Burnout Protector, a previously described mobile health web application 13 . Age below 18 was the only exclusion criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, all data was collected in accordance with scientific standards specified by Switzerland’s Federal Act on Research Involving Human Beings 15 and in compliance with the national ethical guidelines on the handling of personal data in the field of medicine issued by the Federal Data Protection Commissioner of Switzerland 16 . All respondents provided informed consent to their anonymized data being used for research 13 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations